Safety and effectiveness of docetaxel combinated with S-1 for patients with incurable recurrent squamous cell carcinoma of the head and neck - Morita, Naruhiko; Iwae, Shigemichi; Hirayama, Yuji; Yonezawa, Koichiro; Furukawa, Tatsuya (European Journal of Oncology and Environmental Health, 2015)
Background and aim of the work: Therapeutic options for patients with advanced platinum-refractory squamous cell carcinoma of the head and neck (SCCHN) are limited. The aim of this study was to determine whether docetaxel (DOC) combined with S-1 (a 5-fluorouracil derivative) is a safe and effective alternative therapy for recurrent, incurable SCCHN that can be administered on an outpatient basis. Methods: We retrospectively investigated the therapeutic outcome and adverse effects of this treatment in 14 patients ineligible for platinum-based therapy because of renal dysfunction, poor overall health, and refractory disease. The patients included 13 men and 1 woman (median age, 64 years; range, 45-79 years). The primary tumor sites were the larynx (n = 6), oropharynx (n = 5), and hypopharynx (n = 3). DOC was administered intravenously for 3-4 weeks at 20-30 mg/m2, and S-1 was administered orally twice daily for 2 weeks at 80-120 mg/day followed by rest for 1-2 weeks. Results: Grade ≤2 hematotoxicity manifesting as leukopenia (n = 3), neutropenia (n = 2), and anemia (n = 4) was observed. Non-hematotoxic adverse effects were grade 2 fatigue (n = 2) and anorexia (n = 1); 1 patient had a grade 4 anaphylactic reaction. The median survival time was 10 months; survival rates after 6 months and 1 year were 64.3% and 32.7%, respectively. Conclusions: The DOC and S-1 regimen caused mild adverse effects and is therefore feasible for ambulatory administration as a salvage treatment for SCCHN patients ineligible for platinum-based chemotherapy.